Phytotherapy for Insomnia: A Review of the Most Important Effective Medicinal Plants in Treating Insomnia According to References of Iran - Abdolrahim Kazemi Vardanjani (Journal of Global Pharma Technology, 2016)
Sleep is a complex biological pattern and one of the circadian rhythm. Insomnia referring to difficulty falling asleep or staying asleep, or lack of sleep, which is tonic and refreshing, is one of the most common disorders of this pattern. Some of the complications of sleep deprivation are weakened immune system, reduced glucose tolerance, reduced hypothalamic-pituitary-adrenal axis activity during subsequent days, hypertension, decreased level of maximum ability to exercise, non-dependently increased risk of cardiovascular events, and talent. In the light of the significance of sleep, appropriate treatment of insomnia, and high prevalence of insomnia in the community, a strategy to treat insomnia can be development of a specific therapeutic strategy and nature-based, complementary medicines. This review article seeks to report the effective medicinal plants on insomnia according to the ethnobotanical references of Iran. According to the findings, 17 plant species from 11 families have been used for prevention and treatment of insomnia n Iran.